Integration of the Blind: Ideals and Reality - Andrejauskas, Vladas (Problemos, 1994)
The idea of social integration of the blind is universally recognized. However, the idea in most cases is interpreted abstractly, i.e., without any consideration of its link with social life. This leads to the revival of the old fashioned view, namely, that of segregation of the blind. The paper criticizes the simplified understanding of social integration of the blind.